Extreme hyperferritinemia without associated HLH in a patient with T‐cell lymphoma. Issue 11 (16th November 2022) - Lau, Grace; Dougherty, Sean C.; Friedman, Lisa; Wispelwey, Brian
Abstract: Extreme hyperferritinemia has historically been associated with a short list of rare diagnoses, including hemophagocytic lymphohistiocytosis (HLH). However, hyperferritinemia is not specific for HLH in the adult population. Among other more common causes, T‐cell lymphoma and other malignancies warrant evaluation prior to considering more rare diagnoses.